Mechanical Properties of Titanium Diboride Particles Reinforced Aluminum Alloy Matrix Composites: A Comprehensive Review - V. Mohanavel; M. Ravichandran; V. Anandakrishnan; Alokesh Pramanik; M. Meignanamoorthy; Alagar Karthick; M. Muhibbullah (Advances in Materials Science and Engineering)
Aluminum alloys with silicon, magnesium, and copper were extensively used alloying elements in various applications because of their excellent properties. In recent decades, aluminum matrix composites (AMCs) are an advanced engineering material widely utilized in diverse engineering applications, including aircraft, automobile, marine, and shipbuilding, owing to their low density, lightweight, good stiffness, superior strength, and good tribological properties. Aluminum is abundant and its use is as vast as the ocean. It is also the most used matrix material in the composite arena. Therefore, incorporating a ceramic particle into a relatively soft aluminum matrix improves hardness, strength, stiffness, creep, fatigue, and wear properties instead of the conventional materials. This article is an assay to review and spotlight some recent works on the mechanical behaviors of aluminum-based titanium diboride reinforced metal matrix composite. This review article concentrates on the mechanical properties and the fabrication processes of Al-TiB2 composites to provide a valuable reference to nurture future research precisely.